The Effect of Business Competition and Capital: Grocery Store Revenue in Kedawung Grati, Pasuruan Regency, Indonesia - Nunuk Indarti; Nurus Sobakh; Rizka Rahmadani Purwanti (Cita konsultindo, 2023)
The purpose of this study was to determine the effect of business competition on the income of grocery stores in Adirogo Hamlet. To find out the effect of capital on grocery store income in Adirogo Hamlet. To find out the effect between business competition and capital on grocery store income in Adirogo Hamlet. This study uses quantitative research using multiple linear regression analysis, where the technique will test hypotheses that will state there is an influence individually or jointly between the independent variable (X) and the dependent variable (Y). What acts as a variable X1 is business competition, X2 is capital and Y is grocery store revenue. Data were obtained using a closed questionnaire Likert scale and five alternative answers. The subjects in this study were grocery store business actors. The subjects in this study were 30 respondents. In this study, instrument testing used validity tests and reliability tests. While the data analysis uses descriptive statistics, classical assumption tests are as follows: normality test, linearity test, heteroscedasticity test, and multicollinearity test, as well as multiple linear analysis. The result of the analysis after going through the process of processing and analyzing multiple linear regression data that has been carried out using SPSS 22 for windows is that there is an influence between business competition variables and capital on grocery store revenue of Fcalculate 248.706 > 2.74 Ftable with a significance of 0.000 < 0.05.